Inquiry-based learning - Lee, Tze Jiun; Kamarudin, Nurzatulshima; Talib, Othman; Hassan, Aminuddin (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Inquiry-based learning is not a new topic to be discussed among the educators, yet some researches with the similar topics had been done since 50 years ago. Scientific inquiry needed a person to see our world in various ways or think out of the box and offer some justifications according to the proof obtained from their work. Hence, different background of people would have different interpretation of inquiry. Various perspective of views about ‘inquiry’ will give important messages to whoever wishes to shift their learning or teaching strategy from traditional ‘cookbook’ to inquiry-based learning or instructional.